The Effect of Cognitive Restructuring Techniques on Reducing Somatic Symptoms in A Patient at Jemursari Hospital - Putri, Dinda Syahda; Amriana, Amriana (Proceedings Of International Conference On Islamic Counseling Studies (ICONICS), 2025)
This study aims to determine the influence of the Cognitive Restructuring technique in reducing somatic symptoms in an inpatient at RSIS Jemursari Surabaya. Somatic symptoms are physical complaints that cannot be fully explained by medical factors but are closely related to psychological conditions such as anxiety and irrational thoughts. The research employed a Single Subject Research (SSR) method with an A–B–A–B design. The subject was a female patient experiencing dizziness, palpitations, and nausea without clear medical causes. Data were collected through interviews, observation, a simple somatic symptom scale, and field notes. Data were analyzed using a descriptive narrative and comparative approach to examine changes in symptom scores across phases. The results revealed a 56.4% reduction in somatic symptoms from the initial to the final phase of intervention. The patient demonstrated improved ability to identify, evaluate, and replace irrational thoughts with more rational perspectives, allowing her to manage health-related anxiety more adaptively. These findings indicate that the application of the Cognitive Restructuring technique has a positive influence on reducing somatic symptoms and enhancing the patient’s psychological well-being.